Edukasi Dan Pemeriksaan Boraks Dengan Bahan Alami Pada Jajanan Sekolah Menengah Atas - Mamay Mamay; Muhammad Hadi Sulhan; Riki Ananda (Jurnal Abdi Masyarakat Kita, 2022)
Borax is a food additive which is prohibited from being used in food. Toxic effects of borax have been found to be harmful to human health. This compound is still widely abused in food samples. Detection of the presence of borax in the sample can be done with the use of natural materials. This community service aims to provide education that can increase the understanding of high school student participants about the dangers of borax and the identification with natural indicator such as turmeric (Curcuma longa), azalea flowers (Rhododendron concina) and red soka flower (Ixora auminta). The method used in the form of counseling and training on borax detection in samples with test paper from turmeric extract, azalea flower extract and red soka flower extract. In the implementation of the service, it was found that there was a change in understanding of borax and its toxic effects from 58% to 96% of science class students and 27% to 87% of social studies students. In the borax examination training, 92% of science student participants and 88% of social studies students were able to perform an examination with natural ingredients using test paper of turmeric extract, azalea flower, red soka flower. From the service process, it was found that, most of the participants knew about borax as a additive food which is prohibited from using and is harmful to health and can carry out a borax examination using natural indicators from turmeric, azalea flowers and red soka flowers.